Semantic spaces of Persian light verbs : a constructionist account - Family, Neiloufar (Brill's studies in South and Southwest Asian languages, 2014)
In this book, Neiloufar Family exposes the semantic organization of light verb constructions in Persian. By clustering constructions based on semantic properties, she provides an insightful and more global view of a system that has been notoriously difficult to classify.